Bookmakers et parieurs entre rue et tripot - Emmanuel Roudaut (Revue Française de Civilisation Britannique)
This paper examines the concern expressed on the issue of gambling in Victorian England. In the 1840s, a series of scandals led to an increase in the repression of gambling houses. Attempts were also made to moralise the turf. By the end of the century, the rowdiest and seediest aspects of race courses had been eliminated. However, attention now focused on new forms of off-course betting on horses, made possible by the rise of the popular press and the development of new technologies. The widespread success of ‘street-betting’ among the working class was the cause of a new ‘moral panic’ in late-Victorian years.